Can employment subsidies and greater labour market flexibility increase job opportunities for youth? Revisiting the Italian On-the-job Training Programme - Giuseppe Tattara; Marco Valentini (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2009)
The CFL (On-the-job Training) Programme was introduced in Italy in 1985 with the aim of reducing youth unemployment. The new programme offered employers two main advantages: it exempted them almost completely from payment of payroll taxes and it provided them with virtually the only opportunity to employ people on a basis of fixed-term contracts. The paper looks at the employment impact of the programme among a subgroup of eligible workers in the north Italian provinces of Treviso and Vicenza and finds that firms taking part increased employment more than non-participating firms by almost 5 %. Employers had a strong positive reaction to the tax subsidies and to the softening of the rigid employment code. The overall effect of the programme on youth employment in Treviso and Vicenza was however limited, registering only a 1 % increase, mainly because about 80 % of firms never participated.
Keywords: 330; Lohnkostenzuschuss - Auswirkungen; Beschäftigungseffekte; Jugendarbeitslosigkeit; Arbeitslosigkeitsbekämpfung; zusätzliche Arbeitsplätze; Personaleinstellung; Jugendliche; befristeter Arbeitsvertrag; arbeitsmarktpolitische Maßnahme; on-the-job training; junge Erwachsene; berufliche Integration; Ausbildungsförderung; Italien